Concordância entre comunidades planctônicas em um reservatório no Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Different organisms may reveal similar patterns in their responses to abiotic and / or biotic factors, suggesting that these organisms are concordant. Some authors suggest that searching for surrogate groups would improve conservation planning and biomonitoring programs. The main goal of this study was to quantify the concordance between phytoplankton and zooplankton community in a small Brazilian Cerrado reservoir (PCH Mosquitão). Procrustes analysis demonstrated no relationships between phytoplankton and zooplankton in this reservoir. Some groups belonging to phytoplankton and zooplankton showed a weak concordance. Moreover, only phytoplankton community were predictable by environmental variables, indicating that phytoplankton and zooplankton communities are responding differently to the environmental gradients. These results suggested that the use of surrogate groups is not recommended in this reservoir.
Keywords: Grupos substitutos; Comunidades planctônicas; Hidrelétrica; Fitoplâncton; Zooplâncton; Surrogates; Community; Hydroelectric; Phytoplankton; Zooplankton; CIENCIAS BIOLOGICAS